Brunei Darussalam : Report on External Sector Statistics Mission (Remote) (July 26-29, 2020). (IMF Staff Country Reports; Country Report ;, 2022)
An External Sector Statistics (ESS) technical assistance (TA) mission was conducted remotely to Brunei Darussalam, during July 26-29, 2020, aimed at improving the quality of ESS, in line with the authoritiesa' request. This is the most recent TA mission on ESS to Brunei Darussalam following a previous one that took place more than 16 years ago by the IMF's Statistics Department.